1980
DOI: 10.1073/pnas.77.3.1278
|View full text |Cite
|
Sign up to set email alerts
|

Could poly(A) align the splicing sites of messenger RNA precursors?

Abstract: In general, poly(A)mRNA appears to be derived from larger nuclear RNA precursors. The maturation of these precursors involves excision of sequences of variable length from within the molecule and splicing of the remaining structural and coding sequences. The mechanism by which this process occurs is not known. It does not appear to operate solely through the recognition of a defined primary sequence or through the formation of a consistent secondary structure. We propose an alternative model in which poly(A) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This observed dichotomy in the phylogenetic distribution of polyadenylated RNA has been interpreted in terms of the function of poly(A) sequences (12), but the possibility that the dichotomy may be only apparent and result from the failure of the isolation procedures for poly(A) RNA as applied to procaryotes has not been seriously considered.…”
Section: Introductionmentioning
confidence: 99%
“…This observed dichotomy in the phylogenetic distribution of polyadenylated RNA has been interpreted in terms of the function of poly(A) sequences (12), but the possibility that the dichotomy may be only apparent and result from the failure of the isolation procedures for poly(A) RNA as applied to procaryotes has not been seriously considered.…”
Section: Introductionmentioning
confidence: 99%
“…Sev-eral reports have pointed out that low-molecular-weight RNAs can form short regions of base pairing around splice sites and therefore may be involved in splicing by forming RNA-RNA base pairing over the splice junctions (23,25,27,35,42). Bina et al (10) have suggested that the poly(A) tails of the nuclear transcripts are involved in splicing by forming a triple helix with the splice junctions, thereby orientating the exons and introns in a proper configuration for the cleavage and ligation event. This triple helix formation makes use of Hogstein and reverse-Hogstein base pairing (6) in addition to the normal Watson and Crick base pairings.…”
Section: Gene For Adenovirus Pvi 473mentioning
confidence: 99%
“…20 min [40]. The splicing reaction is apparently enzymatically controlled [9] and presumably guided by small nuclear RNPs (snRNP) [41] and perhaps by the 3'-poly(A) sequence of mRNA [42].…”
Section: Rnp-associated Ribonucleasesmentioning
confidence: 99%